146k views
5 votes
Please Help! 15 Points. Which of the following can be used to rewrite the expression (3)(2+c)? There are two correct answers. A. Commutative Property of Multiplication B. Associative Property of Addition C. Associative Property of Multiplication D. Commutative Property of Addition

1 Answer

5 votes

Answers:

A. Commutative Property of Multiplication

D. Commutative Property of Addition

=======================================

Step-by-step explanation:

The commutative property of multiplication is the idea we can multiply two numbers in any order. The rule is x*y = y*x

An example would be 2*3 = 3*2 since both sides result in 6.

The same applies to 3*(2+c) because it can be written as (2+c)*3. Simply flip the two factors 3 and (2+c).

--------------------

A similar idea is the commutative property of addition. This rule says that we can add two numbers in any order we want.

x+y = y+x

An example would be 7+9 = 9+7 because both sums result in 16

Using this rule, we can rewrite 2+c as c+2

Therefore 3(2+c) is the same as 3(c+2)

--------------------

We can't use any associative properties because we would need to have 3 terms being either added or 3 terms being multiplied, for associative rules to apply.

For instance 1+(2+3) = (1+2)+3 is an example of the associative property of addition. An example of the associative property of multiplication would be 3(7*9) = (3*7)*9

User Jeril Kuruvila
by
5.6k points